# Find x and y if y= 3x-1 and 2y-3x = 12

### 3 Answers | Add Yours

We need to solve :

y = 3x - 1 ...(1)

2y - 3x = 12 ...(2)

substitute y = 3x - 1 in (2)

=> 2(3x - 1) - 3x = 12

=> 6x - 2 - 3x = 12

=> 3x = 14

=> x = 14/3

y = 3*(14/3) - 1

=> y = 13

**The solution of the system of equations is (14/3 , 13)**

Given the equations:

y = 3x-1

2y - 3x = 12

We need to solve for x and y .

We will use the substitution method to solve

We will substitute with y= 3x-1 into the second equation.

==> 2 ( 3x-1) - 3x = 12

==> 6x - 2 - 3x = 12

==> 3x = 14

==> x = 14/3

Now we will substitute to find y.

==> y= 3x-1 = 3(14/3) -1 = 14 - 1 = 13

**Then the answer is x= 14/3 and y= 13**

The system of equations y= 3x-1 and 2y-3x = 12 is to be solved.

y= 3x-1 ...(1)

2y-3x = 12 ...(2)

(1) can be written as 3x = 1 + y and (2) can be written as 3x = 2y - 12

Now equating the values of 3x gives an equation in y that is 1 + y = 2y - 12

2y - y = 1 + 12

y = 13

3x - 1 = 13

3x = 14

x = 14/3

The solution of the given set of equations is x = 14/3 and y = 13